Anatomy of Regional Disparities in the Slovak Republic - Jarmuzek, Mariusz (IMF Working Papers; Working Paper ;, 2009)
This paper examines economic growth and various dimensions of regional disparities in Slovakia. We find that regional disparities in the levels of GDP per capita, labor productivity, and labor utilization have widened since 2000, coinciding with the time that Slovakia initiated negotiations on EU accession. Notwithstanding ?-divergence in the levels, there was conditional ?-convergence in the growth rates of GDP per capita and labor productivity. Improvements in total factor productivity were the main engine of growth of GDP in all regions. Sustaining growth and reducing disparities will require increasing the labor utilization ratio and improving the structural and policy determinants of productivity in the eastern regions. The main policy priorities are to improve transportation infrastructure, enhance cost competitiveness through greater regional differentiation in wages and further decentralization of collective bargaining, and increase accumulation of human capital.